Improvements to cassava-maize intercropping systems in southern Nigeria - Nwokoro, C.C. (ETH Zurich, 2021)
Cassava-maize intercrop is a traditional and the most popular cassava-based cropping system in southern Nigeria where farmers allocate > 60% of their farmland to intercropping in a typical cropping season. Besides that the system is ecologically adapted to the region, it facilitates a quick recovery from food and cash shortages at planting seasons caused by seed and cash investments in farming operations in every cropping season, .i.e., through food and income generated from maize harvest ~ 3 to 4 months after planting (MAP), before cassava can be harvested ~ 5 to 11 months later. However, suboptimal planting density, poor soil fertility, and inadequate nutrient management are among the identified agronomic management practices contributing to the poor productivities of cassava and maize in the system in farmers' fields. The average cassava and maize yield in Nigeria are about 8 and < 1.5 Mg ha-1, respectively against their attainable yields of > 45 and 8 Mg ha- 1. Cassava and maize are major sources of dietary energy for > 500 million Sub-Saharan Africa inhabitants, thus any attempt towards improving the productivity of both crops would likely have positive impacts on food and income security in that region. However, since the smallholder farmers in this region are financially constrained and risk-averse, they are apprehensive to invest in external fertilizer input to manage cassava-based farms. Therefore, there is a need to understand the economic implications of fertilizer investment as a possible yield improvement option capable of addressing the poor productivity from cassava and maize in farmers' fields. The main objective of this thesis was to investigate the potentials of increasing cassava and maize densities and fertilizer application and management in increasing the productivity of cassava-maize intercropping systems in southern Nigeria. Furthermore, I aimed to understand some of the underlying mechanisms behind the crop responses to treatments. The treatments' effects on cassava storage root yield and qualities (.i.e. starch yield, contents of starch, cyanide, and NPK nutrient elements), and profitability or otherwise of investment in NPK fertilizer in the smallholder systems were also investigated. In a set of 126 non-replicated multilocation trials (MLTs) conducted in the states of Anambra, Benue, Cross River, Ogun, and Oyo in southern Nigeria, I investigated between 2016 and 2018, the yield and profitability potentials of two densities of cassava (LC: low cassava density of 10,000 plants ha-1 versus HC: high cassava density of 12,500 plants ha- 1) and maize (LM: low maize density of 20,000 plants ha-1 versus HM: high maize density of 40,000 plants ha-1) managed with two regimes of NPK fertilizers targeting either for a yield improvement in cassava (FC: 75 kg N, 20 kg P, and 90 kg K ha-1) or maize (FM: 90 kg N, 20 kg P, and 37 kg K ha-1), compared to a control treatment without fertilizer applied (F0) in the intercropping systems. Maize yield increased with increased density (HM) by an average of 11% over two years of the study relative to the low maize density (LM) treatment. Averaged across years, fertilizer application increased maize yield by 15% in the FC regime and 19% in the FM regime. In the first year, cassava storage root yield increased by 16% (4 Mg ha-1) due to an increase in planting density and 14% (4 Mg ha-1) due to fertilizer application (across both regimes). In the second year, intercropping cassava with the HM density reduced cassava yield by 7% (1.5 Mg ha-1) relative to the intercrop of cassava with the LM density; however, this effect was counteracted by fertilizer application. Average value cost ratio of investment in fertilizer was higher in the FM regime treatment than in the FC regime. Cassava yield was similar between the two fertilizer regimes. Maize yield was higher in the FM regime treatment than in the FC regime. Revenue from maize contributed > 80% of the combined (intercrop) revenue in the intercropping systems. To study the effects of the maize density and fertilizer regime on cassava and maize growth and development, and on the efficiency of the intercropping systems on interception of photosynthetically active radiation (IPAR), radiation use efficacy (RUE), and yields of both crops, I established 8 completely randomized researcher-managed trials (RMTs) with 4 replicates in the states of Anambra, Benue, and Cross Rivers between 2017 and 2019. Based on my observation that the HC plant density performed better than the LC density, with or without fertilizer application, the low-density cassava treatment was dropped after the first year of the MLTs and was not tested in the RMTs. The FM regime led to better growth and development of cassava and maize than the FC regime. Although the intercrop of cassava with the HM density reduced cassava biomass production, the combined intercrop biomass production was higher in the high-density treatment compared with the low-density intercrop treatment. This resulted in an average of 71% IPAR without fertilizer application and 80% with fertilizer application over the 2 years of the study. Averaged over 2 years, fertilizer application led to a 35% increase in RUE (by 1 g DM biomass m-2 MJ-1 IPAR) in cassava-high maize density (C-HM) intercrop treatment compared to without fertilizer application. In the RMTs, the FC regime generally increased cassava storage root yield compared with the FM regime. Similarly, the FM regime increased maize yield compared with the FC regime. I also investigated the effects of fertilizer and maize density on starch yield, contents of starch, cyanide, and NPK nutrient elements in storage roots sampled at 3 months intervals beginning from 3 months after planting (MAP) until the 12th MAP only in the Anambra state RMTs. Over both years, the FC regime resulted in 12% (1.4 Mg FW h-1) higher starch yield compared with the FM regime; starch yield was least without fertilizer application. Cyanide content in the storage root samples was higher in the control treatment (F0) samples, especially in the first year (2017) when the crops experienced drought. NPK contents in storage roots increased with fertilizer application but were reduced at intercropping with the HM density compared with the LM density treatment. In conclusion, the current 10,000 cassava plants ha-1 for cassava-maize intercropping can be replaced with a higher density of 12,500 plants ha-1 using TME 419 at intercropping with 40,000 maize plants ha-1. At this planting density recommendation, the system can be managed with either the FM regime or the FC to further improve yields from cassava and maize. Higher IPAR, RUE, and soil moisture retention in the intercropping system can also be achieved at these recommended planting densities and fertilizer applications. However, it is not always profitable to invest in fertilizer in the intercropping systems in southern Nigeria hence, fertility knowledge of targeted fields is necessary for a profitable fertilizer investment decision. For specific yield targets when fertilizer application is required, it is recommended that the system be managed with the FM regime if higher maize yield is required otherwise, the system should be managed with the FC regime when higher storage root and starch yields are targeted. Most importantly, during fertilizer formulation and recommendation, nutrient ratios should be such that meet the needs of specific fields and target yields. To further reduce the risk of cyanide poisoning especially during limited rainfall or in drought-prone regions, cassava production should be managed with fertilizer; either the FC or the FM regime.